Evolutionary origins of the SARS-CoV-2 sarbecovirus lineage responsible for the COVID-19 pandemic - Boni, Maciej; Lemey, Philippe; Jiang, Xiaowei; Lam, Tommy; Perry, Blair; Castoe, Todd; Rambaut, Andrew; Robertson, David (New Zealand Science Review, 2022)
-